The Influence of Work-Life Balance and Work Stress on Job Satisfaction With Psychological Capital as a Mediating Variable (on Civil Servant Employees of the BKD DIY) - Sakina, Munadiyah Wulansari; Sutanto, Hery (Universitas Mercu Buana, 2025)
Maintaining job satisfaction among civil servants is essential for ensuring the effectiveness and efficiency of public service delivery. In this context, factors such as work-life balance, work stress, and psychological capital play a crucial role. This study investigates the influence of work-life balance and work stress on job satisfaction, with psychological capital serving as a mediating variable among civil servants at the Regional Personnel Agency (BKD) of the Special Region of Yogyakarta (DIY). The population in this study consists of all BKD DIY employees, and the sampling technique employed is exhaustive sampling, resulting in a total of 85 respondents. Data were collected through the distribution of offline, hard-copy questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results indicate that work-life balance has a significant positive effect on job satisfaction, while work stress has a significant negative effect. In addition, psychological capital significantly mediates the relationship between work-life balance and job satisfaction, as well as the relationship between work stress and job satisfaction. These findings highlight the importance of strengthening psychological capital to enhance job satisfaction among civil servants.